Association of Aortic Pulse Wave Velocity with the Severity of Coronary Artery Disease in Patients with Acute ST Elevation Myocardial Infarction (Cardiovascular Journal, 2014)
Background: Arterial stiffness assessed noninvasively with aortic pulse wave velocity (PWV) has been associated with atherosclerosis in the coronary arteries and also cardiovascular mortality. The aim of this study was to evaluate the association between aortic PWV and severity of coronary artery disease (CAD) in patients with acute ST elevation myocardial infarction (STEMI). Methods: This cross sectional analytical study was conducted over 200 acute STEMI patients who were purposively selected and agreed to do coronary angiogram during index hospital admission. Assessment of aortic PWV was performed noninvasively with the commercially available SphygmoCor system using applanation tonometry with high fidelity micromanometer on the day before angiogram. Study subjects were subdivided into two groups on the basis of PWV. In group I: aortic PWV was d 10 m/sec and in group II: aortic PWV was> 10 m/sec. One hundred patients were included in each group. Angiographic severity of CAD was assessed by vessel score, Friesinger score and Leaman score. Results: Vessel score 0 and 1 were significantly higher in group I (p